Desenvolvimento de materiais carbonados dopados com nitrogênio para aplicação em processos adsortivos e catalíticos - Crestani, Larissa (2024)
Nitrogen doping (N-doping) has been widely applied in materials synthesized under controlled conditions. However, its impact remains unclear when employed in converting various residues into cost-effective and efficient adsorbents and catalysts. This research investigated the influence of different pyrolysis conditions on N doping in residues from biogenic silica production, aiming to produce advanced materials for application in environmental remediation processes. Initially, the biogenic silica residue obtained from carbonized rice husks was treated with acid and base to remove impurities. This treatment was effective due to the improving properties such as surface area, porosity, functionality, and methylene blue adsorption (97%). Subsequently, an experimental design was conducted to investigate the effects of urea percentage (N source) and different pyrolysis temperatures to optimize desired properties. A total of 10 N-doped materials were obtained, and their characteristics were extensively studied to infer each specific effect. The doping of nitrogen groups was effective, without significantly affecting the crystalline structure of carbon. Urea percentage impacted material properties, as the percentage of urea increased, increasing the basicity and pore size while reducing area and volume. While a lower percentage of urea decreased the electronic properties (band gap). In addition, nitrogen doping enhanced adsorption and photocatalysis efficiency, although with reduced removal percentages as urea content increased. Thus, this study demonstrates how to modulate the complexity of doping process conditions to obtain improved and specific properties for pre-carbonized residues. The material obtained with a temperature of 600°C and a urea percentage of 21.7% (C600N21) showed promise, exhibiting favorable characteristics and notable performance in paracetamol (68%) and diclofenac (98%) removal and degradation. Its behavior was investigated in adsorption and photocatalysis kinetics, in which the pseudosecond order model presented the best fit to the data. Mineralization showed an efficiency of 70% and 97%, respectively. These results shows that it is possible to dope residues to obtain materials with significant changes in physical, chemical and electronic properties, along with enhanced performance in the adsorptive and catalytic processes.